Debts and interest in the construction industry a guide to The Late Payment of Commercial Debts (Interest) Act 1998 - Johnston, Scott, 1971- (Thomas Telford, 1999)
The late payment of commercial debts is a serious concern for the majority of UK businesses. The Late Payment of Commercial Debts (Interest) Act 1998 was implemented to address this important issue by the introduction of a statutory right to interest on debts. This title provides practical assistance for creditors and debtors in dealing with the act and claims for interest on debts.